A Comparative Study Of Nominative And Accusative Cases In Urdu And English - Nimra Tariq , Minahil Iftikhar , Farhat Fatima , Naveed Ahmad Khan (Migration Letters, 2024)
The study aims to explore the similarities and differences between the nominative and accusative cases in English and Urdu, with a focus on how they are used in practical contexts. The study employs Chomsky’s Case theory (1981) to examine the characteristics of nouns and determine whether they fall under the nominative or accusative case in any given language. In addition to the case theory, qualitative methods and descriptive content analysis are used to analyze Urdu and English sentences. The researchers have used their own intuitions while collecting the data. The results show that in Urdu, the case markers are generally added to the end of the noun or pronoun that they modify, whereas in English, the case markers are usually separate words that come before or after the noun or pronoun. Despite these distinctions, both languages use case markers to indicate grammatical information about the connections between nouns and pronouns in a sentence. The study provides a comprehensive analysis of the Urdu sentences and their English translations which shows that positioning of nominative case is almost the same in Urdu and English languages but accusative has different positions in Urdu and English. Accusative case comes after verb in English but in Urdu it comes before verb.